The Progressive Legal Perspective of Legal Justice in Customary Dispute Resolution Related to Natural Resources - Akbar, Muhammad; Maisa; Permana, Mohamad Didi; Rusli, Hazmi (Magister of Law, Faculty of Law, University of Mataram, 2023)
The absence of special arrangements regarding customary law has the potential to cause inferiority in the position of customary law compared to the substance of national law in customary disputes relating to natural resources. This study seeks to analyze and formulate the idea of ​​resolving customary disputes over the management of natural resources in a progressive legal perspective to achieve justice. The results of the study confirmed that the problems of customary disputes related to the management of natural resources, especially those that occurred in the territories of indigenous peoples, made the position of customary law weaker compared to national law. This happens because regulations regarding indigenous peoples have not been ratified. Legal efforts to settle natural resource customary disputes to achieve justice in a progressive legal perspective need to be regulated through the establishment of a Perppu (Government Regulation in Lieu of Law) to facilitate the position of customary law in resolving customary disputes in the field of natural resource management. In the Perppu, it is hoped that there will be confirmation regarding the enactment of the conception of legal pluralism so that customary law has an equal position with national law in customary disputes over natural resource management.